Is there a regional aspect in the growth and economic development policies in the current structure of local self-governments? - Cassetti, Luisa (2015)
In the context of the financial crisis of the last years,a centralizing tendency has grown, leaving asidethe attribution of powers to Regional Governments. The margin of the economic intervention of those entities has been reduced to the management and  implementation of the solutions previously developed and imposed by the Central Government.In this article, the outstanding author presents us a legal analysis, on the basis of the Italian case, as to whether it is reasonable to chase social-economic development, excluding the system of local self-governments, or relegating them to a purely passive role.